Prisons and Security Challenges in a Democratic Nigeria - Adebisi, Kolawole Shittu (2015)
Survival of every nation- state is a function of her ability to cope with security challenges. The security sector in Nigeria in recent years is faced with constant threat from within. It is against this background that this paper examines the roles of Nigerian Prison Service as an integral part of the security configuration of the country and the challenges facing the outfit towards stemming the tide of security problems facing the country. It further analyzes the symbiotic relationship between the prison system of a nation and its security challenges. Related data were obtained through secondary source and were descriptively analysed. The study concluded that Nigerian Prison is not well equipped to fulfil its mandate. Consequently, the paper recommends that training in modern day techniques of prison administration and effective funding are panacea for improved performance of Nigerian prison service. Keywords: Prison service, Security challenges, Democratic Nigeria, Nation-state